Factors influencing continuance intention towards on-demand ridesharing services - Aw, Eugene Cheng Xi (2017)
On-demand ridesharing services have seen unprecedented growth in recent times, threatening to replace traditional business models. The identification of critical service performance factors which contribute to customer satisfaction and loyalty is essential for businesses success. The purpose of this research was to investigate important factors that influence customers’ continuance intention towards on-demand ridesharing services in Malaysia. This study applied Means-End Theory as the foundation to examine the relationship between perceived attributes (perceived service innovativeness, perceived personalization, and perceived usefulness of online customer review system), service personal values, perceived value, satisfaction, and continuance intention towards on-demand ridesharing services. Furthermore, the moderating role of technology readiness and trust were examined in the research model. The subjects of this study consists of individuals who have experienced using on-demand ridesharing services in Malaysia. Through a quantitative research approach, this study utilizes a purposive sampling method to collect 280 useable responses through online and face-to-face self-administered surveys. Data was analysed using Partial Lease Square Structural Equation Modelling (PLS-SEM). The result articulated that perceived personalization, perceived usefulness of online customer review system and service personal values was found to be the significant predictors of perceived value towards on-demand ridesharing services. Subsequently, perceived value positively affects satisfaction, and that in turn, has a positive impact on the continuance intention outcome. Moderating effect of technology readiness has been found in the relationship between perceived attributes (perceived service innovativeness and perceived personalization) and perceived value. In addition, customer satisfaction and continuance intention were found to be moderated by trust. Mediating role of perceived value was found in the relationship between perceived personalization and customer satisfaction, perceived usefulness of online customer review system and customer satisfaction, service personal values and customer satisfaction. Important implications for the industry’s service providers are further discussed.